Formulation and Evaluation of Lercanidipine HCL Loaded Nanomicelles - Hala Mohammed Fatih; Ahmed, Kawther Khalid (Iraqi Journal of Pharmaceutical Sciences, 2026)
Among the strong calcium channel blockers, lercanidipine hydrochloride (LER) has been shown to be useful in reducing blood pressure by acting on L-type calcium channels. Nevertheless, the main drawback of lercanidipine is that it is a BCS class II medication with poor solubility and a 10% oral bioavailability because of significant first pass metabolism. The goal of this study is to use the thin film hydration process to generate and assess lercanidipine nanomicelles utilizing soluplus in conjugation with other surfactants/polymers at different ratios in order to boost the solubility of virtually insoluble LER. Six formulations were prepared and analyzed for their micelles size, polydispersity index (PDI), encapsulation efficiency (EE%), and in-vitro release. The optimum formula was determined to be the one prepared using soluplus, poloxamer188 and tween80(50mg). Micelle size was found to be 62.26 nm, with PDI 0.233 and EE (88.8%). An in-vitro release study was conducted, and the results showed that the chosen formula (solu/p188/tween50) released the entire dose of drug in 75 minutes with 94% release, compared to only 53% for pure drug.These findings indicate the strong potential of employing LER HCl micelles in dosage form formulation.